Principles Governing the Treatment of Victims of Armed Conflicts from the Perspective of Islam and International Humanitarian Law: With Emphasis on the Status of Prisoners of War and Detainees - Mostafa Fazaeli (پژوهش تطبیقی حقوق اسلام و غرب, 2021)
From the perspective of international humanitarian law (IHL), the main purpose of parties to an armed conflict shall be exclusively weakening the enemy’s forces and repelling them out of the battlefield. Accordingly, several principles are formed aimed at controlling military activities, means and ways of war of the parties to the conflict and their treatment of the individuals and groups caught by the adversary. What has been accepted by international community after several centuries and has transformed the law of war into humanitarian law, has been reaffirmed by Islam from the beginning. Furthermore, in spite of some diversionary and extremist claims and conducts, there are some principles derivable from sources, tradition and transcendental teachings of Islam complying with which can play a transformational role in improving the status of war victims and preserving their human dignity and value. Reconsidering these principles, especially in the condition of the emergence of some extremist groups and violent behaviors of fighters attributing themselves to Islam, has become a new necessity. These principles include some common principles between Islam and IHL and certain principles specific to legal and ethical system of Islam. The present article undertakes the analysis and examination of common principles of Islam and IHL that indicates the influence of Islamic thoughts on the development of these principles. However, there are certain principles of conduct in Islam relative to protecting victims of armed conflicts that require another study.